A comparative study on language teacher educators' ideal identities in China: more than just finding a middle ground. Issue 2 (15th March 2019) - Yuan, Rui
ABSTRACT: This paper reports on a comparative study that investigates English language teacher educators' ideal identities from the dual perspectives of language teachers and teacher educators in China. Drawing on data from focus and individual interviews, the findings of the study reveal a range of identities such as 'practical expert, ' 'model' and 'learner, ' which were perceived by the two parties (i.e. the languages teachers and teacher educators) as pivotal for an ideal language teacher educator. On the other hand, the two parties held differing views about some identities such as 'researcher' and 'scholar' due to the contextual influences in the higher education context. The study offers some useful implications for teacher educators to develop their professional identities and improve their effectiveness in educating teachers.